ER nurses : true stories from America's greatest unsung heroes - Patterson, James, 1947-; Eversmann, Matt; Mooney, Chris (Little, Brown and Company, 2021)
"James Patterson and Matt Eversmann, #1 bestselling coauthors of Walk in My Combat Boots, powerfully present the medical frontline heroes who work to save our lives every day: E.R. Nurses. Around the clock, across the country, these highly skilled and compassionate men and women sacrifice and struggle for us and our families. You have never heard their true stories. Not like this. From big-city and small-town hospitals. From behind the scenes. From the heart. This book will make you laugh, make you cry, make you understand. When we're at our worst, E.R. nurses are at their best."--Amazon.com.